2012
DOI: 10.1371/journal.pone.0034831
|View full text |Cite
|
Sign up to set email alerts
|

Access Rate to the Emergency Department for Venous Thromboembolism in Relationship with Coarse and Fine Particulate Matter Air Pollution

Abstract: Particulate matter (PM) air pollution has been associated with cardiovascular and respiratory disease. Recent studies have proposed also a link with venous thromboembolism (VTE) risk. This study was aimed to evaluate the possible influence of air pollution-related changes on the daily flux of patients referring to the Emergency Department (ED) for VTE, dissecting the different effects of coarse and fine PM. From July 1st, 2007, to June 30th, 2009, data about ED accesses for VTE and about daily concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…In fact, many EPA monitoring sites no longer measure PM 10 . Although all types of PM can activate inflammation, produce oxidative stress, and promote thrombosis and coagulation [1], [38], something specific to larger particles may be important in VTE as suggested by Martinelli et al [36]. Although our results could be interpreted as support for a significant role of larger particles, we cannot rule out the possibility that some specific component of PM 2.5 is important (even though the overall PM 2.5 peak occurred in the winter).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In fact, many EPA monitoring sites no longer measure PM 10 . Although all types of PM can activate inflammation, produce oxidative stress, and promote thrombosis and coagulation [1], [38], something specific to larger particles may be important in VTE as suggested by Martinelli et al [36]. Although our results could be interpreted as support for a significant role of larger particles, we cannot rule out the possibility that some specific component of PM 2.5 is important (even though the overall PM 2.5 peak occurred in the winter).…”
Section: Discussionmentioning
confidence: 50%
“…We attempted to minimize the effect of variable delay by grouping VTE cases per week (the mode of the delay distribution). Nevertheless, a study of VTE (302 cases over two years) in Verona, Italy found a correlation between daily coarse particle levels and the daily number of VTE cases [36]. Incorporation of lag-times into this analysis failed to show a correlation with VTE.…”
Section: Discussionmentioning
confidence: 84%
“…Further, the role of air pollution on venous thromboembolism (VTE) remains inconsistent, with some studies indicating an increased risk among those who had higher air pollution exposure [29] , [30] . However recent prospective studies do not support this association [31] , [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have determined a positive correlation between PM 2.5 levels and respiratory tract disease prevalence, hospitalization rates, and daily death rates [16,17]. These relations are more marked in the elderly, pregnant women, babies, adolescents, subjects with a history of cardiopulmonary disease and other susceptible populations [18][19][20]. One study of a seven-year period in the USA (from 2000 to 2007) showed that every 10 µg / m 3 decrease in PM 2.5 extended life spans by 0.35 years [21].…”
Section: Particulate Mattermentioning
confidence: 99%